What impact will the rise... of the emerging economies in the South have on South-South cooperation... (2012)
Presents the views of seven experts in South-South relations, in relation to the assumption that economic interactions between countries of the South are more beneficial than those between the North and the South.
Keywords: SOUTH SOUTH RELATIONS